ICT-based agricultural extension services and women’s empowerment: Evidence from Nigeria and Ethiopia - Lambrecht, Isabel B. (International Food Policy Research Institute, 2023)
Digital tools and extension services are promising options to deliver optimized agronomics at scale. Yet, technical solutions and advisory systems will fail to produce the intended outcomes if they do not manage to deliver their messages to farmers, or if farmers are unable to benefit from this advice. Women, in particular, often have less access to digital tools and also have less decision-making power in agriculture. Therefore, they may find it more difficult to benefit from these tools, to leverage them for more empowerment and for a more gender-equitable society. Our study provides a comprehensive analysis of the issues through the lens of the Reach-Benefit-Empowerment and Transform (RBET) framework through a combination of a strategic literature review related to gender in the rapidly developing field of ICT-based agricultural extension services on the one hand, and quantitative data analysis from two different settings—Ethiopia and Nigeria—on the other hand. We used original survey data collected in 2023 with one male and one female respondent (if available) from 900 households in Northern and Southwestern Ethiopia and 1,080 households in northern Nigeria, respectively. We analyzed which aspects or dimensions of empowerment are associated with ICT access, how this is influenced by other social markers such as economic status and age, and which gendered constraints are there for women to be reached, benefited and empowered through agricultural support tools. We reflected on the actions that might leverage digital tools toward a transformation for more gender-equitable relations within their households and communities.